Answer:
![x \approx 2.740646096](https://img.qammunity.org/2023/formulas/mathematics/high-school/i19w9qp1iondabp42k4kz2g6gcjp801e4s.png)
Explanation:
Given:
![x\log_(10)x=1.2](https://img.qammunity.org/2023/formulas/mathematics/high-school/emf0kfdvu5moktfw67vhilsupbveuulnzy.png)
Rewrite so that it's equal to zero:
![\implies x\log_(10)x-1.2=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/50civl4x8fkzhsh2b7y4zmzjdftt5g0x06.png)
Therefore:
![\implies f(x)=x\log_(10)(x)-1.2](https://img.qammunity.org/2023/formulas/mathematics/high-school/6bf4hjc0bu0n0ef15y3844z0hg4psjlt7q.png)
Differentiate the function:
Use the product rule to differentiate
:
![\textsf{Let }u=x \implies (du)/(dx)=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/eb6mhulgwpirwd9ttesiaftzpq2qrncqkg.png)
![\textsf{Let }v=\log_(10)(x) \implies (dv)/(dx)=(1)/(x \ln 10)](https://img.qammunity.org/2023/formulas/mathematics/high-school/a4crui583e20jna5gasb306ebnbq0j69uj.png)
![\begin{aligned}\implies (dy)/(dx) & = u(dv)/(dx)+v (du)/(dx)\\& = (x)/(x \ln 10)+\log_(10)(x)\\& = (1)/(\ln 10)+\log_(10)(x)\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qy6tjdipx26y92bhoyrizw8lyjifoxx6ix.png)
![\implies f'(x)=(1)/(\ln 10)+\log_(10)(x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/61bhbiot0yugjjtrziq0zdjqegh0dzyjvf.png)
![\implies f'(x)=(1+\ln 10 \log_(10)(x))/(\ln 10)](https://img.qammunity.org/2023/formulas/mathematics/high-school/uw34fdv4z4vpeh6m5m17vt5vile3tvl1s1.png)
Newton-Rhapson iteration formula
![x_(n+1)=x_n-(f(x_n))/(f'(x_n))](https://img.qammunity.org/2023/formulas/mathematics/high-school/aueku07h9um8isam7wck9sekosv851yz3j.png)
Substitute the function and its derivative into the formula, replacing x with
:
![\implies x_(n+1)=x_n-(x_n\log_(10)(x_n)-1.2)/((1+\ln 10 \log_(10)(x))/(\ln 10))](https://img.qammunity.org/2023/formulas/mathematics/high-school/9dz6b1jy8xtsijwebogx8lz1uqo2qjewju.png)
![\implies x_(n+1)=x_n-(x_n\ln 10\log_(10)(x_n)-1.2\ln 10)/(1+\ln 10 \log_(10)(x_n))](https://img.qammunity.org/2023/formulas/mathematics/high-school/5xn9rlo1ddr6hvkmcbi3yeb83nj9qmrjtm.png)
Therefore, the iteration formula is:
![x_(n+1)=x_n-(x_n\ln 10\log_(10)(x_n)-1.2\ln 10)/(1+\ln 10 \log_(10)(x_n))](https://img.qammunity.org/2023/formulas/mathematics/high-school/oclm1odnal81x7ytqytx06txddn8xq24pw.png)
Let
![x_0=3](https://img.qammunity.org/2023/formulas/mathematics/high-school/l5kd7hevghz48e4s4jv8nvkt6clh5hejk8.png)
Substitute this into the formula and carry out 3 iterations:
![\implies x_(1)=3-(3\ln 10\log_(10)(3)-1.2\ln 10)/(1+\ln 10 \log_(10)(3))=2.746149035](https://img.qammunity.org/2023/formulas/mathematics/high-school/10q4gi780gqbm9me5bzbp62c398eigvfgk.png)
![\implies x_2=2.740648841](https://img.qammunity.org/2023/formulas/mathematics/high-school/lp28co1qgmlxtil1mdnyxl6qukq6ip761v.png)
![\implies x_3= 2.740646096](https://img.qammunity.org/2023/formulas/mathematics/high-school/m8ilepwo3oi3n841lg41b5i7op8ivtouek.png)